Deferred dreams, defiant struggles : critical perspectives on Blackness, belonging, and civil rights - Johnson, Violet Showers; Graml, Gundolf; Williams Dockery, Patricia (FORECAAST., 2018)
This volume sheds light on how to construe the contemporary political vicissitudes of the Black experience and the ongoing struggle for agency, belonging, and civil rights. It offers a fresh look at familiar concepts such as activism and belonging and models innovative approaches for studying the African diasporic experience in the 21st century.